DETECTION OF SAPOVIRUS IN BRAZILIAN PIG FARMS - HOCHHEIM, J. R.; GRAVINATTI, M. L.; SOARES, R. M.; GREGORI, F. (Ars Veterinaria, 2021)
Sapoviruses (Caliciviridae) are considered important gastroenteritis worldwide affecting animals and humans. In pig farming, the epidemiology has not completely understood, because can affect all stages of production, with symptomatic (diarrhea) or asymptomatic pigs. The aim of our study was investigated Sapovirus occurrence in Brazilian pig farms. A total of 166 fecal samples of pigs, with different ages, from Minas Gerais, São Paulo and Mato Grosso States were submitted to RT-PCR reactions and confirmed with nucleotide sequencing of Sapovirus RdRp gene. In total, six (3.61%) samples were positive and four of them had partial RdRp gene sequenced, putatively belonging to GVII.1 genogroup, also previously reported in swine herds in Brazil.